2021
DOI: 10.1016/j.jaim.2021.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Use of complementary and alternative medicine among patients with cancer in a sub-Himalayan state in India: An exploratory study

Abstract: Background The use of complementary and alternative medicine (CAM) is widespread among cancer patients in India. Objective The present study elucidated usage patterns of CAM and the factors responsible for its adoption among the patients with cancer, and the therapeutic impact of CAM. Materials and methods This was a questionnaire-based study, conducted among patients with cancer in a tertiary care hospital in a sub-Himalayan city. Data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
8
1
Order By: Relevance
“…As for the information regarding T&CM, the primary sources were informal sources like family, friends, or other patients. The proportion of nonprofessional group in our findings (82.9%) was higher than Indonesia (70.9%) [ 55 ], India (67.9%) [ 59 ], as well as Australia (77.0%) [ 60 ], the United States (60.0%) [ 61 ]. While medical personnel accounts for a significant proportion as the source of information in the United States (17.8%) and Australia (39.0%), but in Asia, it is meager like our result (0.7%) or Indonesia (7.3%) [ 55 ].…”
Section: Discussioncontrasting
confidence: 49%
“…As for the information regarding T&CM, the primary sources were informal sources like family, friends, or other patients. The proportion of nonprofessional group in our findings (82.9%) was higher than Indonesia (70.9%) [ 55 ], India (67.9%) [ 59 ], as well as Australia (77.0%) [ 60 ], the United States (60.0%) [ 61 ]. While medical personnel accounts for a significant proportion as the source of information in the United States (17.8%) and Australia (39.0%), but in Asia, it is meager like our result (0.7%) or Indonesia (7.3%) [ 55 ].…”
Section: Discussioncontrasting
confidence: 49%
“…Evidence from existing literature highlight the association of initial alternate medicine usage to delay in presentation and advanced stage in diagnosis. 4,12,13 In this study, 89.67% of those subjects who had history of alternate medicine usage presented in advanced stage (stage III or IV) versus 50.74% of those who did not. In this subgroup, progressive increase in the period of delay was associated with corresponding increase in the percentage of presentation in advanced stage, from 89.68% in those having more than 1 month delay to 92.22% in those having more than 3-month delay to 99.16% in those having more than 6-month delay, which were greater than the corresponding values for the total sample as a whole.…”
Section: Discussionmentioning
confidence: 59%
“…Evidence from existing literature highlight the association of initial alternate medicine usage to delay in presentation and advanced stage in diagnosis. 4 12 13…”
Section: Discussionmentioning
confidence: 99%
“…In another study by Gerber (Gerber et al 2014 ), 38.2% of midlife women in Qatar had used CAM in the previous 12 months. Pandey et al reported in India that 46.2% of their study sample used CAM (Pandey et al 2021 ).…”
Section: Introductionmentioning
confidence: 98%